Advance Care Planning—Complex and Working: Longitudinal Trajectory of Congruence in End-of-Life Treatment Preferences: An RCT. (June 2021) - Lyon, Maureen E.; Caceres, Sarah; Scott, Rachel K.; Benator, Debra; Briggs, Linda; Greenberg, Isabella; D'Angelo, Lawrence J.; Cheng, Yao I.; Wang, Jichuan; ,
Context: The effect of advance care planning (ACP) interventions on the trajectory of end-of-life treatment preference congruence between patients and surrogate decision-makers is unstudied. Objective: To identify unobserved distinctive patterns of congruence trajectories and examine how the typology of outcome development differed between ACP and controls. Methods: Multisite, assessor-blinded, intent-to-treat, randomized clinical trial enrolled participants between October 2013 to March 2017 from 5 hospital-based HIV clinics. Persons living with HIV(PLWH)/surrogate dyads were randomized to 2 weekly 60-minute sessions: ACP (1) ACP facilitated conversation, (2) advance directive completion; or Control (1) Developmental/relationship history, (2) Nutrition/Exercise. Growth Mixed Modeling was used for 18-month post-intervention analysis. Findings: 223 dyads (N = 449 participants) were enrolled. PLWH were 56% male, aged 22 to 77 years, and 86% African American. Surrogates were 56% female, aged 18 to 82 years, and 84% African American. Two latent classes (High vs. Low) of congruence growth trajectory were identified. ACP influenced the trajectory of outcome growth (congruence in all 5 AIDS related situations) by latent class. ACP dyads had a significantly higher probability of being in the High Congruence latent class compared to controls (52%, 75/144 dyads versus 27%, 17/62 dyads, p = 0.001). The probabilities of perfect congruence diminished at 3-months post-intervention but was then sustained. ACP had a significant effect (β = 1.92, p = 0.006, OR = 7.10, 95%C.I.: 1.729, 26.897) on the odds of being in the High Congruence class. Conclusion: ACP had a significant effect on the trajectory of congruence growth over time. ACP dyads had 7 times the odds of congruence, compared to controls. Three-months post-intervention is optimal for booster sessions.